The Influence of Good Corporate Governance, Profitability, Leverage on Company Value Moderated by Company Size - Putri, Siti Qibtiyah Septiani; Suryani, Desi; Yulianto, Agung (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: Company value is one of investor’s consideration before making invesment decision. The aim of the research carried out is to analyze influence, profitability, GCG (Good Corporate Governance), company size and leverage on company value. Design/methodology/approach: In this research, a population is applied in the form of food and beverage sector manufacturing companies on the BEI (Indonesian Stock Exchange) list for 2019-2022. As the following research sample uses a purposive sampling method, so that what is obtained is a total of 19 business entities. This research applies a type of data in the form of secondary data. In carrying out the research, data analysis was used in the form of multiple linear regression. Findings: A conclusion was obtained in the form of profitability and leverage having an influence on the value of the company, in contrast to managerial ownership, independent board of commissioners, audit committee, and company size as moderators having no influence on the value of the company. Paper type: Research Paper